Getting Access to Water: Property Rights or Public Policy Strategies?. (February 2013) - Aubin, David; Varone, Frédéric
Water is subject to heterogeneous uses that put pressure on it and create rivalries between competing users. With this paper we analyse the conditions under which challengers are successful in gaining access to the resource and in imposing a change of behaviour on the incumbent users. We ask whether the acquisition of property rights is the only means for a challenger to get access to the resource. The empirical study compares eleven 'most different' cases of water rivalries in four water basins. We show that two main 'paths' explain success: either the challenger activates a property right and negotiates a solution at no cost for the incumbents or he or she activates a public policy that grants him or her a credible alternative to a negotiated agreement. Thus, the challenger must select the kind of rule, property right, or public policy that supports their position and then elaborate an appropriate strategy to impose this rule.